CHANGING LIVELIHOOD STRATEGY OF THARU COMMUNITY PEOPLE (International Journal of Food and Nutritional Sciences, 2022)
The study entitled Changing Livelihood Strategy of Tharu People in Baijnath Rural Municipality ward no. 8, Banke. Tharu is one of the indigenous as well as ethnic groups of Nepal. They have their own tradition, language, costumes, sprits, norms, belief, values, religion and cultural. The changing livelihood strategy of the Tharu people of ward no. 8 is the Title of the research. The broad objective of this study is to analyze the changing livelihood strategies of and the specific objectives is to investigate the social and economic changes of the Tharu community of study area and to find out the changing livelihood pattern of Tharu community in present changing context. The study is descriptive methods in the nature and sociological perspectives are used. Simple random and purposive samplers were used for study. Tharu are the indigenous as well as ethnic people of study area. They have unique culture, own language and tradition and they are most ancient, simple, honest and backward community. The structure of house gradually changes from old house to cemented house according to their economic condition. The Tharu of study area have adopted new agricultural technology, use of improvement seed, fertilizer, pesticides, practices of intensive and mixed cropping pattern, use of advanced agricultural tools and equipment. They have changed their traditional way for celebrating feast and festivals from lengthy, expensive, big gathering and too much liquor consumption to less expensive, short duration, limited liquor consumption and small gathering.